420,256 views
10 votes
10 votes
X 1 2 3 4 5 Y 4 7 10 13 16Given the table, write an expression for the function, and describe what it does.A) y= 2x. Y is double x.B) y= 3x. Y is triple x.C) y= 3x +1. Y is three times x plus 1.D) y= 3x -1. Y is three times x minus 1.

User Deduper
by
3.0k points

1 Answer

17 votes
17 votes

Answer:

The correct equation is y = 3x + 1 and it shows that y is three times x plus 1.

Option C.

Step-by-step explanation:

Given the table in the question, we're asked to write an expression for the function, and describe what it does. To do this, let's pick each of the given equations and determine which of them is the correct equation for the function.

Let's pick the 1st equation: y = 2x. From our table, when x = 1, y = 4.

Let's see if the equation will give us y = 4 when we insert x = 1;


\begin{gathered} y=2x \\ y=2(1) \\ y=2 \end{gathered}

We can see that the 1st equation isn't the correct one.

Let's pick the 2nd equation: y = 3x. If we put x = 1, let's see if we'll have y = 4;


\begin{gathered} y=3x \\ y=3(1) \\ y=3 \end{gathered}

We can also see that the 2nd equation isn't the correct one.

Let's pick the 3rd equation: y = 3x + 1. Let's see what happens when x = 1;


\begin{gathered} y=3x+1 \\ y=3(1)+1 \\ y=3+1 \\ \therefore y=4 \end{gathered}

So we can see that when x = 1, y =4 just as given in the table. Let's try one more value of x, x = 2;


\begin{gathered} y=3x+1 \\ y=3(2)+1 \\ y=6+1 \\ \therefore y=7 \end{gathered}

We can also see that when x = 2, y = 7 just as given in the table.

Therefore the correct equation is y = 3x + 1 and it shows that y is three times x plus 1.

User Jim Nutt
by
2.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.